(untitled) (Conferencea, 2022)
In the scientific article named as "Development of engineering and creative abilities of students in drawing classes on exercises of geometric and graphic design”, details of pedagogical experiments conducted by the authors and aimed at achieving the results mentioned in the title of the article are presented.